REFLEKSI REVOLUSI PEMIKIRAN DALAM PERSPEKTIF AL-QUR’AN MENUJU INDONESIA EMAS 2045 - Otong Surasman (EL-ADABI : Jurnal Studi Islam, 2025)
This study will examine the concept of Reflection of the Ideal Thought Revolution in the Perspective of the Qur'an, an effort to dig up information from the holy book of the Qur'an on how to reorganize the mentality of the nation that has experienced character damage, to repair it again in order to achieve a golden Indonesia in 2045. This study uses a qualitative approach by conducting an in-depth study of the text of the holy book of the Qur'an, as its main reference source, also using the literature of the interpretation book to provide ease in understanding the text of the holy book of the Qur'an related to improving the mental character of the Indonesian nation, towards a more advanced Indonesian nation and the realization of a just, prosperous, safe and prosperous society. The temporary conclusion by understanding the concept of Reflection of the Ideal Thought Revolution excavated from the holy book of the Qur'an, the noble ideals of the Indonesian nation will be realized to achieve a golden country in 2045.